2021
DOI: 10.1155/2021/6991002
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Left Atrial Appendage Occlusion in Treating Patients with Previous Ischemic Stroke on the Disease Recurrence

Abstract: Background and Objective. Thrombolytics and anticoagulants are conventional drugs for ischemic stroke (IS) treatment, whereas some patients have unfavorable responses to these drugs. The disease presents a relatively high recurrence rate. This investigation attempted to unveil the long-term effect of left atrial appendage occlusion (LAAO) in treating patients with previous IS on the disease recurrence. Methods. A total of 120 patients with IS admitted to Tangdu Hospital from July 2016 to September 2017 were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The proportion of stroke caused by AF suddenly increased from 1.5% in the age of 50-59 years to 23.5% in the age of 80-89 years. A large number of studies have shown that 91-100% of patients with non-valvular AF have thrombosis in the left atrial appendage (LAA) (4,5). The treatment of AF has become a real challenge for cardiologists and electrophysiologists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of stroke caused by AF suddenly increased from 1.5% in the age of 50-59 years to 23.5% in the age of 80-89 years. A large number of studies have shown that 91-100% of patients with non-valvular AF have thrombosis in the left atrial appendage (LAA) (4,5). The treatment of AF has become a real challenge for cardiologists and electrophysiologists.…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of AF has become a real challenge for cardiologists and electrophysiologists. Although oral anticoagulants are currently the standard protocol for preventing AF from stroke, due to various reasons such as bleeding risk, compliance, and cost, 50% of AF patients remain unsuitable for oral anticoagulant therapy (5). For AF patients who are unable to tolerate oral anticoagulants, left atrial appendage closure (LAAC) is an alternative therapy to lower the risk of adverse events.…”
Section: Introductionmentioning
confidence: 99%